ANALISIS HUBUNGAN ANTARA MOTIVASI, KOMPENSASI DAN IKLIM ORGANISASI DENGAN KEPUASAN KERJA GURU SMK KABUPATEN BIREUEN - Nurliana Nurliana; Saiful Bahri; Said Mulyadi (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
Teacher job satisfaction is one of the factors that must be considered, if teachers feel satisfaction at work, it will create an atmosphere full of togetherness, having the same responsibilities, a good communication climate and also high work morale so that the goals of the organization or school can be achieved effectively. maximum. But on the other hand, if the teacher is not satisfied, it will create a stiff, boring atmosphere and low team spirit. Against the background of this phenomenon, this article discusses the results of quantitative research aimed at finding out the relationship between motivation, compensation and organizational climate and job satisfaction of teachers at the Bireuen Regency State Vocational High School. By using a questionnaire as a data collection instrument, which was analyzed using multiple regression analysis techniques, data analysis showed that motivation had a positive and significant effect on teacher job satisfaction of 0.432, compensation had a positive and significant effect on teacher job satisfaction of 0.287, organizational climate had a positive and significant effect. on teacher job satisfaction of 0.248 and motivation, compensation, organizational climate together have a positive and significant effect on teacher job satisfaction of 54.281. The conclusion obtained is that hypotheses one, two, three and four are accepted or rejected. Ha accepts Ho.